Pengaruh Model Pembelajaran Problem Based Learning pada Materi Hidrolisis Garam terhadap Hasil Belajar Peserta Didik - Debby Maulina Sukmadani; Suryelita Suryelita (Universitas Negeri Padang, 2021)
Presentation on the topic of Salt Hydrolysis can be started from a real problem, using the Problem Based Learning (PBL) model. The PBL model should be able to increase students curiosity to get concepts independently. The purpose of this study was to determine the effect of PBL model on salt hydrolysis lessons about the students learning outcomes in SMAN 1 Ranah Pesisir. This research is quasi experiment with non-equivalent groups post-test only design. Data are normal and homogeneous, as of hypothesis testing uses t-test is done at alpha 0.05, obtained tcount 5,2 and ttable 2,67. The result showed that the learning outcomes on salt hydrolysis lessons between classes using PBL model are higher than conventional model in SMAN 1 Ranah Pesisir.